Pengaruh Locus Of Control (LOC) Terhadap Organizational Citizenship Behavior (OCB) Petugas Rutan Kelas IIB Sumenep - Rahmat Putra Diyanto; Maki Zaenudin (Universitas Islam Kadiri, 2022)
This study aims to determine the effect of Locus of Control on Organizational citizenship behavior of officers at the Class IIB Sumenep State Detention Center. The type of research used in this article is quantitative. The location of the research was carried out at the Class IIB Rutan Sumenep. With a sample number of Sumenep Rutan officers as many as 57 respondents. The sample in this study were all officers of the Sumenep Rutan who were still on active duty. The variables used in this study consisted of independent variables and dependent variables. The dependent variable in this study is the organizational citizenship behavior variable, while the independent variable used is the Locus of Control variable. The data obtained were analyzed using SPSS 23. Based on the results obtained, it can be concluded that Locus of Control has a positive and significant effect on Organizational citizenship behavior.